2021
DOI: 10.1136/jech-2020-216200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring multilevel social determinants of depressive symptoms for Tanzanian adolescents: evidence from a cross-sectional study

Abstract: BackgroundDepression has substantial and enduring impacts for adolescents, particularly those living in poverty. Yet, evidence on its determinants in low-income countries remains scarce. We examined the social determinants of depressive symptoms for Tanzanian adolescents.MethodsWe used cross-sectional data for 2458 adolescents (aged 14–19), to describe associations with depressive symptoms within and across five domains—demographic, economic, neighbourhood, environmental and social-cultural—using linear mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Low self-esteem (as compared with high self-esteem) and engaging in both school and paid work (as compared with exclusive schooling) were associated with poorer mental health at baseline ( 25 ), and our study found modest protective intervention effects on these pathways. However, the pathway indicators examined here do not fully explain the effects on mental health.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Low self-esteem (as compared with high self-esteem) and engaging in both school and paid work (as compared with exclusive schooling) were associated with poorer mental health at baseline ( 25 ), and our study found modest protective intervention effects on these pathways. However, the pathway indicators examined here do not fully explain the effects on mental health.…”
Section: Discussionmentioning
confidence: 53%
“…The secondary goal of this study was to acquire a mechanistic understanding of impacts on mental health by estimating effects on potential pathways. We selected time-variant indicators, aligned with the intervention curriculum, topics, or goals, that were identified in a previous study as important factors related to depressive symptoms in the baseline sample of this evaluation ( 25 ): employment/education status, having a romantic partner, self-esteem, quality of life, and locus of control (LOC).…”
Section: Methodsmentioning
confidence: 99%
“…In our analysis, being a student was associated with a higher probability of CMD, in comparison to those who worked. Since other research has found that studying is protective of mental health among adolescents (Prencipe et al, 2021), it is possible that the higher odds of CMD among students had to do with the pandemic situation, when schools were suspended or classes moved online. Similar to other studies (Patrick & Schulenberg, 2013), we found working to be associated with higher odds of substance use.…”
Section: Discussionmentioning
confidence: 99%
“…This measure has proven to be reliable and valid across a range of child and adolescent ages and in diverse cultural contexts [e.g., (56,57)], including in other samples in Vietnam (58). It has been widely used with school-age children [e.g., (59)(60)(61)] and adolescents in diverse low-, middle-and high-income countries [e.g., (62)], including the 51 nations participating in the Health Behaviour of School-Age Children Study co-ordinated by WHO [e.g., (63)]. However, it is more useful for examining within-country differences and patterns of change within individuals than for comparing levels of life satisfaction between countries (64).…”
Section: Psychological Wellbeingmentioning
confidence: 99%